Assessment of neurotoxicity induced by different-sized Stöber silica nanoparticles: induction of pyroptosis in microglia. Issue 27 (1st July 2019) - Du, Qiqi; Ge, Dan; Mirshafiee, Vahid; Chen, Chen; Li, Min; Xue, Changying; Ma, Xuehu; Sun, Bingbing
Abstract : Stöber silica nanoparticles induce size-dependent pyroptotic cell death in microglia while with minimum cytotoxicity in microendothelial cells and neurons. Abstract : With the wide application of Stöber silica nanoparticles and their ability to access the brain, it is crucial to evaluate their neurotoxicity. In this study, we used three in vitro model cells, i.e., N9, bEnd.3 and HT22 cells, representing microglia, microendothelial cells and neurons, respectively, to assess the neurotoxicity of Stöber silica nanoparticles with different sizes. We found that Stöber silica nanoparticles almost had no effect on the viability of bEnd.3 and HT22 cells. In contrast, they induced size-dependent toxicity in N9 cells, which represent the residential macrophages of the central nervous system. Further mechanistic study demonstrated that the toxicity in N9 cells was related to their surface silanol display. In addition, we demonstrated that Stöber silica nanoparticles induced the production of mitochondrial ROS, release of IL-1β, cleavage of GSDMD, and occurrence of pyroptosis in N9 cells. Features of pyroptosis were also observed in primary microglia and macrophage J774A.1. In conclusion, these findings were helpful for the safety consideration of Stöber silica nanoparticles considering their wide applications in our daily life.